The Analysis of Primary Students’ Learning Obstacles on Plane Figures’ Perimeter and Area using Onto-Semiotic Approach - Rina Milinia; Mohammad Faizal Amir (IAIN Syekh Nurjati Cirebon, 2022)
AbstractPrimary school students frequently encounter plane figures’ perimeter and area. Using an onto-semiotic approach, this study examine students' learning challenges when learning the plane figures’ perimeter and area. As part of the didactic design research, this study used an interpretive paradigm. The study included 25 fourth-grade students in one of elementary school in Sidoarjo, Indonesia. Data was gathered through tests, interviews, and documentation, as well as descriptive analysis techniques. The results showed that students face three types of learning obstacles, i.e. ontogenic, epistemological, and didactic. Students have difficulty describing plane figures, understanding mathematical situations in problems, and using mathematical procedures to solve problems using the onto-semiotic approach. This study examines students' reactions to learning about the plane figures’ perimeter and area. Furthermore, the findings of this study serve as a starting point for educators, practitioners, and researchers in developing new didactic designs. So that grade four primary students can overcome the obstacles discovered.Keywords: learning obstacles, plane figures, onto-semiotic approach. AbstrakSiswa sekolah dasar sering menjumpai keliling dan luas bangun datar. Dengan menggunakan pendekatan onto-semiotik, penelitian ini mengkaji hambatan belajar siswa dalam mempelajari keliling dan luas bangun datar. Sebagai bagian dari penelitian desain didaktik, penelitian ini menggunakan paradigma interpretif. Penelitian ini melibatkan 25 siswa kelas empat di salah satu sekolah dasar di Sidoarjo, Indonesia. Pengumpulan data dilakukan melalui tes, wawancara, dan dokumentasi, serta teknik analisis deskriptif. Hasil penelitian menunjukkan bahwa siswa menghadapi tiga jenis hambatan belajar, yaitu ontogenik, epistemologis, dan didaktik. Siswa mengalami kesulitan mendeskripsikan bangun datar, memahami situasi matematis dalam masalah, dan menggunakan prosedur matematis untuk menyelesaikan masalah dengan menggunakan pendekatan onto-semiotik. Penelitian ini menguji reaksi siswa terhadap pembelajaran tentang keliling dan luas bangun datar. Selanjutnya, temuan penelitian ini menjadi titik awal bagi pendidik, praktisi, dan peneliti dalam mengembangkan desain didaktik baru. Sehingga siswa kelas empat sekolah dasar dapat mengatasi hambatan yang ditemukan.Kata kunci: hambatan belajar, bangun datar, pendekatan onto-semiotik.